2016
DOI: 10.18632/oncotarget.12689
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion (IVIM) in diffusion-weighted imaging (DWI) for Hepatocellular carcinoma: correlation with histologic grade

Abstract: PurposeTo assess the correlation between DWI diffusion parameters obtained using Intravoxel Incoherent Motion Method (IVIM) and histological grade of Hepatocellular carcinoma (HCC).ResultsAccording to Edmondson-Steiner grade lesions were classified with grade 1 (14), grade 2 (30), grade 3 (18), and grade 4 (0). Apparent Diffusion Coefficient (ADC), perfusion fraction (fp), tissue diffusion coefficient (Dt) median values were statistically different in HCC groups with 1, 2, 3 histological grade (p<0.001). A sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 30 publications
6
59
3
Order By: Relevance
“…We also observed that ADC value indicated better diagnostic value than D or f value alone on evaluating aggressive behavior of bladder cancer. The same conclusions were reported previously in other tumors …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also observed that ADC value indicated better diagnostic value than D or f value alone on evaluating aggressive behavior of bladder cancer. The same conclusions were reported previously in other tumors …”
Section: Discussionsupporting
confidence: 92%
“…The same conclusions were reported previously in other tumors. [20][21][22] Recently, Wang et al 14 observed the IVIM-derived parameters D value showed higher AUC than ADC value (0.894 versus 0.786), for discriminating MIBC that is equivalent to high-aggressive bladder cancer, but no significant difference was observed in f value, which was somewhat different from our results. In our study, the ADC value showed higher AUC than D value (0.895 versus 0.862), and f value showed second-highest AUC (0.873) for discriminating highaggressive bladder cancer.…”
Section: Carcinomas the Adc And D Values Also Could Be Used To Disticontrasting
confidence: 94%
“…One previous study demonstrated that the ADC and ADC slow were higher in low‐grade gliomas than high‐grade gliomas, as the tumor cellularity was associated with the tumor grade; high cellularity often correlated with high‐grade gliomas. Our results are consistent with findings from previous studies in tumors elsewhere in the body . Furthermore, the numerical values of ADC were greater than ADC slow in each group; this was because the ADC slow was derived from the biexponential model and can eliminate the interference of perfusion and maintain the true diffusion.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with findings from previous studies in tumors elsewhere in the body. 32,33 Furthermore, the numerical values of ADC were greater than ADC slow in each group; this was because the ADC slow was derived from the biexponential model and can eliminate the interference of perfusion and maintain the true diffusion. Furthermore, the AUC value of the ADC slow obtained by two radiologists were higher than ADC in distinguishing PD from WM differentiating esophageal carcinoma and a stronger correlation was also found in ADC slow .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies verified that the mean ADC value had a strong relationship with the pathological grades of HCC, and the diagnostic accuracy of the ADC value was moderate to high. In recent years, the intravoxel incoherent motion diffusion‐weighted imaging (IVIM) techniques showed potential for having a further improved diagnostic performance for the pathological grading of HCC . IVIM was able to separate the true water molecular diffusion from microcapillary perfusion.…”
mentioning
confidence: 99%